Viewing tourism : investigating residents experiences and perceptions of different forms of tourism in Ísafjörður, Iceland - Regan, James Anthony, 1991- (2020)
Ísafjörður is the largest town in Ísafjarðardjup, and the capital of Ísafjarðarbær, a municipality containing it and the four towns of Hnífsdalur, Flateyri, Suðureyri and Þingeyri. It is a prominent location for the fisheries sector in the northern Westfjords. It has also has recently seen a rapid expansion in its tourism sector, particularly influenced by a growth in cruise tourism, with a growth in cruise tourist arrivals of 45.8% between 2015 and 2017. This thesis investigated the perceptions and experiences that residents of Ísafjörður had towards tourism. This investigation took the form of an in-depth qualitative study utilising 14 semi-structured interviews. Residents generally had a neutral attitude towards tourism, perceiving both the economic and social benefits of tourism whilst also having experienced the impacts of some undesirable tourist behaviours. They placed value in both the role tourism had in sustaining services in Ísafjörður and the positive impacts of social and cultural exchange to both tourists and residents. Residents were particularly aware of the impacts of tourism upon the area’s environment, something they placed significant value in. They were also concerned, yet optimistic, about the future of tourism in the area, general awareness of the tourism area life cycle model having caused concern that continuing expansion may be unsustainable. While tourism is currently certainly within the development stage, participants in the research were cautious about further investment in tourism. The results of this research suggest that as well as a general plan to manage future tourism growth, specific management actions should be taken in order to limit the impacts of problematic tourist and tour operator behaviours with a disproportionate effect on social harmony. Ísafjörður er stærsta byggðin við Ísafjarðardjúp og einnig stærsti þéttbýliskjarni innan sveitarfélagsins Ísafjarðarbær, en aðrir bæir eru: Hnífsdalur, Flateyri, Suðureyri og Þingeyri. Staðsetning Ísafjarðar á norðanverðum ...